Analisis Vulnerability Sistem Informasi di Universitas Udayana Menggunakan Tool Acunetix Web Vulnerability Scanner - I Putu Adi Yuda; I Gusti Ngurah Anom Cahyadi Putra (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
Now, information technology is developing rapidly. Information systems provide convenience, especially in the field of education such as information systems at Udayana University. In addition, in universities, information systems are also used in elementary schools and high schools. Information systems must have good security. The requirements that must be met are privacy, integrity, authentication, and availability. However, no information system is completely secure. Like the information system at Udayana University has a vulnerability where it is still possible to be attacked by unauthorized parties. System vulnerability has three levels, namely low level, medium level, and high level. This can disrupt a system, and information can be changed by unauthorized parties. Therefore, it is necessary to scan the Udayana University information system to find out system vulnerabilities. The author uses the Acunetix Web Vulnerability Scanner tool. The results of the scanning can be used as a reference for evaluating system vulnerabilities so that further system security can be improved better than before.